Frequência de anticorpos anti-Toxocara em frangos criados em sistema semi-intensivo, no Norte do Paraná, Sul do Brasil - OLIVEIRA, Adilson Cardoso de (2017)
Toxocariasis is an important zoonosis of worldwide distribution. The main way of transmission of the disease to human is the ingestion of soil containing embryonated eggs of Toxocara spp., the etiological agent. Studies have indicated the ingestion of raw or undercooked meat of chickens as another way of transmission. Besides, free-range chickens have been considered a good sentinel for the contamination of soil by Toxocara spp. eggs. The aim of this study was to evaluate the presence of anti-Toxocara antibodies in naturally infected broiler chickens (n=189) slaughtered in an abattoir located in Paraná, southern Brazil. The chickens were reared in a semi-intensive system by small familial farmers (n=7). An ELISA test was performed to detect the presence of anti-Toxocara IgY after serum adsorption with Ascaridia galli extract. An overall seroprevalence of 67.7% (128/189; 95% confidence interval [CI] = 61.1-74.4) was observed. The frequency of positive animals by farm ranged from 29.6% to 100%. The optical density and reactivity index indicated the possible chronicity of infection of the evaluated chickens. Associations between the presence of antibodies and the area where chickens were reared (p = 0.382) or the population density of dogs on the farm (p = 0.785) were not observed. This study shows a high frequency of Toxocara spp. infection in broiler chickens reared in semi-intensive systems and provides significant evidence that chickens are good indicator of environmental contamination by larva migrans agents. Further studies are necessary to assess the risk factors associated with poultry infection and the likelihood of toxocariasis transmission to humans via the ingestion of free-range chicken meat.